2013
DOI: 10.1021/ie3019214
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Process Pathways for Biorefinery Design Using Optimization Tools: A Colombian Case for Conversion of Sugarcane Bagasse to Ethanol, Poly-3-hydroxybutyrate (PHB), and Energy

Abstract: In this paper a techno-economic and environmental analysis for a sugar cane bagasse biorefinery in Colombia is presented as a case study. An optimization procedure is shown in order to select the most promising process pathway for the production of fuel ethanol, poly-3-hydroxybutyrate (PHB), and electricity. Once the optimization procedure was done, the results served as criteria for the selection of technologies and raw materials distribution. The distribution results and technologies were used to feed the kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(25 citation statements)
references
References 59 publications
0
25
0
Order By: Relevance
“…For all technologies the remaining solid fraction is not currently used, however it can be sent to other productive process to take advantage of its polysaccharide fraction and obtain platform chemicals to drive biorefinery products, or a fraction can be used to feed biogas/cogeneration systems and cover the energy requirements of the process and obtain electric power surplus as a new product (Moncada et al, 2013a;Moncada et al, 2013c;Quintero et al, 2013). It is expected higher footprints for higher energy consumption.…”
Section: Environmental Assessmentmentioning
confidence: 99%
“…For all technologies the remaining solid fraction is not currently used, however it can be sent to other productive process to take advantage of its polysaccharide fraction and obtain platform chemicals to drive biorefinery products, or a fraction can be used to feed biogas/cogeneration systems and cover the energy requirements of the process and obtain electric power surplus as a new product (Moncada et al, 2013a;Moncada et al, 2013c;Quintero et al, 2013). It is expected higher footprints for higher energy consumption.…”
Section: Environmental Assessmentmentioning
confidence: 99%
“…In addition, product diversification in a biorefinery concept has demonstrated an important role in enhancing the economic feasibility of second generation biofuels [12]. New biorefinery schemes for the sugarcane sector have been recently presented in the literature integrating first and second biofuel production and other derived chemicals, as butanodiol [13] and poly-3-hydroxybutyrate (PHB) [14], and also considering the integration of third generation biofuels [15]. As a result of these new sugarcane biorefinery concept developments, the authors concluded that the production of chemicals, as well as, closing the CO 2 cycle by algae growth and sequential biodiesel production (third generation biofuel) added to the respective sugarcane biorefinery sustainability, both economically and environmentally.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, this method focus on the conversion pathway, consequently the pretreatments, the separations and the purifications are not considered. The optimization model of Moncada et al [18] established the biorefinery's optimal configuration with respect to the economic, environmental and technical objectives to produce biochemical products and bioenergy. The different biochemical pathways are simulated to obtain accurate mass and energy balances and then compared, but the entire process is not studied.…”
Section: Introductionmentioning
confidence: 99%
“…According to the optimization methods for the process design of biorefineries and especially biorefineries producing butanol [18][19][20][21]26], each model deals with some objectives but it does not exist a complete method that integrate all the steps of a biorefinery. Moreover, no method includes the retroaction of the butanol recovery on the performances of the fermentation.…”
Section: Introductionmentioning
confidence: 99%